2020
DOI: 10.3389/fgene.2019.01355
|View full text |Cite
|
Sign up to set email alerts
|

Functional Annotation of the Transcriptome of the Pig, Sus scrofa, Based Upon Network Analysis of an RNAseq Transcriptional Atlas

Abstract: The domestic pig (Sus scrofa) is both an economically important livestock species and a model for biomedical research. Two highly contiguous pig reference genomes have recently been released. To support functional annotation of the pig genomes and comparative analysis with large human transcriptomic data sets, we aimed to create a pig gene expression atlas. To achieve this objective, we extended a previous approach developed for the chicken. We downloaded RNAseq data sets from public repositories, down-sampled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 69 publications
1
42
0
Order By: Relevance
“…We have previously identified novel macrophage and nervous system specific genes (Hume et al, 2010;Carpanini et al, 2017). In the pig we found that many unannotated transcripts were fragments of known genes; these were highlighted because they shared expression pattern with the annotated fragment of the same gene (Summers et al, 2020). In our study a number of co-expression clusters were found that distinguished the cardiac valves from heart muscle.…”
Section: Discussionsupporting
confidence: 48%
“…We have previously identified novel macrophage and nervous system specific genes (Hume et al, 2010;Carpanini et al, 2017). In the pig we found that many unannotated transcripts were fragments of known genes; these were highlighted because they shared expression pattern with the annotated fragment of the same gene (Summers et al, 2020). In our study a number of co-expression clusters were found that distinguished the cardiac valves from heart muscle.…”
Section: Discussionsupporting
confidence: 48%
“…Transcriptome data for various mammalian tissues generated from 142 RNA-seq experiments (whole transcriptome shotgun sequencing) was collected from publicly available sources. Briefly, human data was from the GTEx (Genotype-Tissue Expression) project 14 , ENCODE (ENCyclopedia Of DNA Elements) project 15 , and 6 Frausto et al 16 ; bat data was from Dong et al 17 ; pangolin data was from Ma et al 18 and Mohamed Yusoff et al 19 ; cat data was from 99 Lives Cat Genome Sequencing Initiative project; dog data was from Hoeppner et al 20 , Lindblad-Toh et al 21 and Sudharsan et al 22 ; ferret and rabbit data was from Chen et al 23 ; hamster and goat data was from Fushan et al 24 ; cow data was from Merkin et al 25 ; and pig data was from Summers et al 26 . Detailed information on accession numbers and tissues for each species was listed in Table S2 in Supplementary data.…”
Section: Transcriptome Data Collectionmentioning
confidence: 99%
“…Based on the data of RNA-seq, the C/EBPα, C/EBPβ, C/EBPδ, C/EBPγ, and C/EBPζ genes are expressed in all 27 adult Duroc tissues, and C/EBPε is expressed only in 5 tissues. Summers et al (2020) created a pig gene expression atlas based on the meta-analysis and demonstrated that C/EBPε is expressed only in a few tissues, and other C/EBP genes are expressed in the majority of tissues [35]. Uhlén et al (2015) studied the expression patterns of the C/EBP genes in 32 human tissues and demonstrated that the C/EBPβ, C/EBPδ, C/EBPγ, and C/EBPζ genes are expressed ubiquitously [36].…”
Section: Discussionmentioning
confidence: 99%